GPs' perspectives on colorectal cancer screening and their potential influence on FIT-positive patients: an exploratory qualitative study from a Dutch context. Issue 1 (2019) - Bertels, Lucinda; Heijden, Sientje van der; Hoogsteyns, Maartje; Dekker, Evelien; Asselt, Kristel van; Weert, Henk van; Knottnerus, Bart
No abstract available